Foldable Solid‐State Batteries Enabled by Electrolyte Mediation in Covalent Organic Frameworks. Issue 23 (30th April 2022) - Guo, Dong; Shinde, Digambar B.; Shin, Woochul; Abou‐Hamad, Edy; Emwas, Abdul‐Hamid; Lai, Zhiping; Manthiram, Arumugam
Abstract: Solid‐state electrolytes with high Li + conductivity, flexibility, durability, and stability offer an attractive solution to enhance safety and energy density. However, meeting these stringent requirements poses challenges to the existing solid polymeric or ceramic electrolytes. Here, an electrolyte‐mediated single‐Li + ‐conductive covalent organic framework (COF) is presented, which represents a new category of quality solid‐state Li + conductors. In situ solidification of a tailored liquid electrolyte boosts the charge‐carrier concentration in the COF channels, decouples Li + cations from both COF walls and molecular chains, and eliminates defects by crystal soldering. Such an altered microenvironment activates the motion of Li + ions in a directional manner, which leads to an increase in Li + conductivity by 100 times with a transference number of 0.85 achieved at room temperature. Moreover, the electrolyte conversion cements the ultrathin COF membrane with fortified mechanical toughness. With the COF membrane, foldable solid‐state pouch cells are demonstrated. Abstract : A high‐performance solid‐state electrolyte by engineering of the molecular channels in lithiated covalent organic frameworks (COFs) is presented. In situ electrolyte mediation in the COF increases charge‐carrier concentration, eliminates interfacial defects, and activates the motion of Li + ions in a directional manner. The COF‐based electrolyte demonstrates reliable electrochemical cyclability in pouch cells.